A Graphene Composite Material with Single Cobalt Active Sites: A Highly Efficient Counter Electrode for Dye‐Sensitized Solar Cells. (18th April 2016) - Cui, Xiaoju; Xiao, Jianping; Wu, Yihui; Du, Peipei; Si, Rui; Yang, Huaixin; Tian, Huanfang; Li, Jianqi; Zhang, Wen‐Hua; Deng, Dehui; Bao, Xinhe
Abstract: The design of catalysts that are both highly active and stable is always challenging. Herein, we report that the incorporation of single metal active sites attached to the nitrogen atoms in the basal plane of graphene leads to composite materials with superior activity and stability when used as counter electrodes in dye‐sensitized solar cells (DSSCs). A series of composite materials based on different metals (Mn, Fe, Co, Ni, and Cu) were synthesized and characterized. Electrochemical measurements revealed that CoN4 /GN is a highly active and stable counter electrode for the interconversion of the redox couple I − /I3 − . DFT calculations revealed that the superior properties of CoN4 /GN are due to the appropriate adsorption energy of iodine on the confined Co sites, leading to a good balance between adsorption and desorption processes. Its superior electrochemical performance was further confirmed by fabricating DSSCs with CoN4  /GN electrodes, which displayed a better power conversion efficiency than the Pt counterpart.